The DUT task: A novel experimental paradigm to investigate the variability of eye movements in whole-text reading for meaning. (12th July 2018) - Kroll, Tobias; Trindade, A. Alexandre; Asikis, Amber; Salas, Melissa; Lau, Marcy; Saenz, Chelsey; Head, Madison; Prematilake, Chalani; Perry, Carolyn
Abstract : This article reports on the development of a novel experimental paradigm for the investigation of the statistical properties of eye movements in whole-text reading, with a focus on variability. Eye movements in reading for meaning were compared to eye movements in proofreading without comprehending, using texts as stimuli that were deemed to be difficult and uninteresting to participants, and hence to effectively preclude reading for meaning in the proofreading condition. Using a linear mixed model for a 4-way ANOVA, variability of total fixation durations and number of fixations was found to be significantly different between conditions, but only for one of the two texts in one of the two designs. This suggests that there may be a correlation between reading proficiency and variability of eye movements, but also that in order to determine this correlation, stimulus texts must be precisely tailored to the participant population.